2016
DOI: 10.5430/air.v5n2p92
|View full text |Cite
|
Sign up to set email alerts
|

Can we obtain viable alternatives to Manning’s equation using genetic programming?

Abstract: Applied water research, like the one derived from open-channel hydraulics, traditionally links empirical formulas to observational data; for example Manning's formula for open channel flow driven by gravity relates the discharge (Q), cross-sectional average velocity (V ), the hydraulic radius (R), and the slope of the water surface (S) with a friction coefficient n, characteristic of the channel's surface needed in the location of interest. Here we use Genetic Programming (GP), a machine learning technique ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Additionally, Bolton and Zanna [2019] showed that a convolutional ANN could skilfully predict small-scale momentum forcing in a quasi-geostrophic ocean model given spatially smoothed output from a simulation, although this was not implemented into a freely-evolving model. Significant advances have also been made in learning symbolic equations and invariant quantities from data [Schmidt and Lipson, 2009;Rudy et al, 2017;Wu and Tegmark, 2018;Zhang and Lin, 2018], which could be applied in Earth system modelling [Gaitan et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Bolton and Zanna [2019] showed that a convolutional ANN could skilfully predict small-scale momentum forcing in a quasi-geostrophic ocean model given spatially smoothed output from a simulation, although this was not implemented into a freely-evolving model. Significant advances have also been made in learning symbolic equations and invariant quantities from data [Schmidt and Lipson, 2009;Rudy et al, 2017;Wu and Tegmark, 2018;Zhang and Lin, 2018], which could be applied in Earth system modelling [Gaitan et al, 2016].…”
Section: Introductionmentioning
confidence: 99%